SARS-CoV-2 Vaccine Strain Selection: Guidance From Influenza. (25th November 2022) - Monto, Arnold S; Lauring, Adam S; Martin, Emily T
Abstract: When first approved, many hoped that the SARS-CoV-2 vaccine would provide long-term protection after a primary series. Waning of immunity and continued appearance of new variants has made booster inoculations necessary. The process is becoming increasingly similar to that used for annual updating of the influenza vaccine. The similarity has become even more apparent with selection of BA.4/BA.5 as the Omicron strain of the updated bivalent (Original + Omicron) COVID-19 vaccines. It is hoped that, if COVID-19 develops winter seasonality, SARS-CoV-2 vaccines will require only annual review to determine if updates are necessary. Recommendations on whom should receive the booster would be based on conditions at that time. Abstract : The COVID-19 mRNA vaccines were recently updated, adding the Omicron BA.4/5 variant as the candidate strain able to produce broadened immunity. This process, akin to annual prewinter influenza strain selection, may become a template for future, necessary COVID-19 vaccine updates.